An Experimental Study of Bond Market Pricing - WEBER, MATTHIAS; DUFFY, JOHN; SCHRAM, ARTHUR (Journal of Finance, 2018)
ABSTRACT An important feature of bond markets is the relationship between the initial public offering (IPO) price and the probability that the issuer defaults. On the one hand, the default probability affects the IPO price; on the other hand, the IPO price affects the default probability. It is a priori unclear whether agents can competitively price such assets. Our paper is the first to explore this question. To do so, we use laboratory experiments. We develop two flexible bond market models that are easily implemented in the laboratory. We find that subjects learn to price the bonds well after only a few repetitions.